The Teaching Of Dasa Sila In Sila Kramaning Aguron-Guron Text From The Communicative Attitude Perspective - Wirawan, I Wayan Ardhi; Wirata, I Wayan; Budhawati, Ni Putu Sudewi; Mahardika, Gede; Ningrat, Jro Ayu (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
This article aims to analyze the teachings of the basic principles contained in the Lontar “sila kramaning aguron-guron” which focuses on the formal objects of communicative attitudes. The focus of the analysis is on the attitude dimension which relies on the teachings of dasa sila, namely ten principles as a guideline for the behavior of sisya (students) in order to improve the quality of spiritual life. This article uses interpretive qualitative methods in analyzing texts using content analysis techniques and hermeneutic methods to interpret the meaning of the text being analyzed. Based on the results of the analysis, it was found that the teachings of the ten principles in the perspective of communicative attitudes emphasize ethics in behavior, both verbally and non-verbally. There are ten human sensory organs that need to be controlled as tools to improve the quality of life of spiritual sisya, consisting of caksuindriya, srotendriya, granendriya, wakindriya, jihwendriya, panindriya, padendriya, paywindriya, pastendriya, and wikindriya. These ten sense organs must be controlled properly and correctly. The basic principles of indriya are a guide to action that must be adhered to by the side in their behavior to improve the quality of life spiritually. The dasa sila, namely ten basic teaching elements of the precepts are communicative actions taught by teachers to their sisya.